EFFECT OF SYZYGIUM CUMINI AQUEOUS EXTRACT ON CARBON TETRACHLORIDE-INDUCED TESTICULAR DAMAGE IN MICE: A HISTOMORPHOMETRY - Susilowati, Rina Priastini; Santoso, Adit Widodo; Sabini, Jasmine Harumi (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
The juwet fruit (Syzygium cumini) is a type of fruit commonly found in Indonesia and is known to contain high levels of antioxidant compounds, potential for protecting reproductive organs from oxidative damage. This study aims to investigate the effects of juwet fruit in protecting the testes from damage caused by CCl4 toxicity in mice. A total of 30 mice were used and divided into six groups: distilled water, 12.5 mg/mL CCl₄, and S. cumini extract at doses of 5, 10, 20, and 40 mg/mL for three weeks.  Parameters assessed included body weight, serum testosterone levels, sperm count, and histomorphometry (seminiferous tubule diameter, germinal epithelium height, and spermatogenic cell counts). The results showed that CCl₄ significantly reduced body weight, the number of spermatogenic cells in the seminiferous tubules, seminiferous tubule diameter, germ cell height, and serum testosterone levels in the mice. The treatment groups receiving extract of juwet fruit at doses of 20 mg/mL and 40 mg/mL showed improvements in testicular function that were not significantly different from the distilled water group. In conclusion, reproductive toxicity induced by CCl₄ in male mice can be ameliorated by administering aqueous extract of juwet fruit at doses of 20 mg/mL and 40 mg/mL.